Biogeochemistry of arsenic and lead in sediment and water amended with biochar - Soares, Matheus Bortolanza (2023)
Potentially toxic elements (PTEs), such as arsenic (As) and lead (Pb), constantly cause the development of diseases in living beings due to the continuous ingestion of water and food with high levels of these elements. Daily anthropogenic practices, such as domestic, health, industrial, agricultural, and mining activities can contribute to the increase in the concentration of As and Pb in soils and sediments exposed to the Earth\'s surface, and this increases the probability of contact with living beings. Although the occurrence of As and Pb in the environment is not necessarily recent, it has become more relevant in recent decades due to their harmful effects and to the global concern to recover natural resources. To restore the functionality of ecosystems contaminated by As and Pb, the scientific community has sought to use remediation techniques to reduce the bioavailable levels of these elements in soil and water. Among them, the use of biochar has stood out due to its ability to immobilize contaminants, supply nutrients, and store carbon. In situ remediation with biochar is an ecological alternative that can be economically viable when compared to other conventional remediation techniques that generate waste and/or are expensive. Biochar is a product of the pyrolysis of organic compounds, and its effectiveness in immobilizing contaminants depends on the manufacturing conditions, including the pyrolysis temperature. In addition, environmental conditions such as redox fluctuation, other factors as high precipitation, and exposure to weather can alter the potential of biochar to (i)mobilize EPTs in the environment. The following itens were evaluated in this study: (i) the effect of biochar pyrolysis temperature on As and Pb dynamics in sediment exposed to environments with total and partial presence of oxygen; (ii) the biogeochemistry of As and Pb in sediment and water submitted to the application of in natura biochar and modified with ferric chloride; and (iii) effects of dissolved organic carbon (DOC) on the competition for specific sorption sites with As. To evaluate the dynamics of As and Pb, several experiments were carried out with sediment and water contaminated with As and Pb due to mining and ore processing. Samples contaminated with As and Pb were conditioned with biochar from sugarcane straw (Saccharum officinarum) pyrolyzed at 350 (BC350), 550 (BC550), and 750°C (BC750), and the potential competition for sorption sites was evaluated in water samples artificially contaminated with arsenate [As(V)]. Sorption competition was performed in the presence of biogenic iron (Fe) (oxyhydr)oxide (BIOS), which is a Fe(III) biomineral widely known to be a natural sink for As. The pyrolysis temperature played a key role in the physicochemical characteristics of the biochar, and this affected the ability to (i)mobilize As and Pb in sediment and water. The application of biochar reduced the β-glucosidase activity and increased the phosphatase activity, which demonstrates the microbiota\'s difficulty in degrading the carbon in the biochar and, at the same time, its ease in providing hydrolase capable of mineralizing phosphate present in organic forms. The aging time of the biochar caused an increase in the bioavailable and exchangeable contents of As to the same extent that it reduced the bioavailable and exchangeable contents of Pb. The increase in bioavailable and exchangeable As contents were related to changes in carbon pools caused by surface oxidation of biochar and by biodegradation promoted by microorganisms. In environments with high precipitation, biochar application increased As release and mobility without affecting As species distribution. The chemical modification of biochar, as a way to improve a water filter, increased the speed and sorption capacity of As and Pb and made biochar modified with ferric chloride a promising alternative for filtering water contaminated with these elements. The presence of DOC from biochar was able to reduce As(V) sorption in BIOS by up to 30%. However, the presence of DOC did not alter As(V) sorption mechanisms in BIOS, which shows that site blocking the main mechanism responsible for reducing As(V) sorption. The biochar was able to reduce the mobility of As in the sediment under environments with partial presence of oxygen. In addition to the change in the mobility of As and Pb, it was verified that the supply of biochar to the sediment considerably increased the DOC content in the solution, which possibly buffered the assimilative biotic reduction of Fe(III) and As(V) and reduced the As methylation.